Computer speech and language - Academic Press (London Academic Press, 1987)
Access available online from 1995- through ScienceDirect
Title from cover.
Keywords: Speech processing systems -- Periodicals; Automatic speech recognition -- Periodicals; Computers -- Periodicals; Linguistics -- Periodicals; Speech-Language Pathology -- Periodicals; Computerlinguïstiek.